Uji Sensitivitas Staphylococcus spp. Terhadap Beberapa Antibiotik Yang Berbeda - Novianti Neliyani Toelle (JURNAL KAJIAN VETERINER, 2019)
Staphylococcus is Gram-positive bacterium that could lead to an acute and chronic disease in poultry. This research was purposed to evaluate the antibiotics susceptibility of these Staphylococcus spp. against commonly used antibiotics in the field. This study uses isolates of Staphylococcus spp. of laying hens which showed a decrease in egg production. To test the sensitivity, antibiotics of amoxicillin and clavulanic acid, tetracycline, gentamycin, colistin sulfate, and enrofloxacin were applied. Results found the sensitivity of Staphylococcus spp. to combination of amoxicillin-clavulanic acid 100%, gentamycin and enrofloxacin 70%.